1993
DOI: 10.1083/jcb.121.1.201
|View full text |Cite
|
Sign up to set email alerts
|

Emilin, a component of elastic fibers preferentially located at the elastin-microfibrils interface.

Abstract: Abstract. The fine distribution of the extracellular matrix glycoprotein emilin (previously known as glycoprotein gp115) (Bressan, G. M., I. Castellani, A. Colombatti, and D. Volpin. 1983. J. Biol. Chem. 258: 13262-13267) has been studied at the ultrastructural level with specific antibodies. In newborn chick aorta the protein was exclusively found within elastic fibers. In both post-and pre-embedding immunolabeling emilin was mainly associated with regions where elastin and microfibrils are in close cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
121
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 26 publications
3
121
1
Order By: Relevance
“…Nevertheless, we found that the FB1 epitope is localized immunoelectron-microscopically in the bundles of subectodermal microfibrils, and that the electrophoretic mobility and immunohistochemical distribution of the FB1 antigen are indistinguishable from those of JB3 antigen, or chicken fibrillin-2 Rongish et al, 1998). The spatial pattern of the fibers demonstrated in this study also overlaps in part the pattern of elastin immunoreactivity in the limb bud (Hurle et al, 1994;Ros et al, 1995;Hurle and Colombatti, 1996), but appears to be more comparable to the pattern of emilin (Hurle and Colombatti, 1996), which is known to be localized in the elastin-microfibril interface (Bressan et al, 1993). On the basis of these and other findings in this study, we discuss the functional and developmental significance of a parallel spatial array of extracellular subectodermal microfibrils.…”
supporting
confidence: 61%
“…Nevertheless, we found that the FB1 epitope is localized immunoelectron-microscopically in the bundles of subectodermal microfibrils, and that the electrophoretic mobility and immunohistochemical distribution of the FB1 antigen are indistinguishable from those of JB3 antigen, or chicken fibrillin-2 Rongish et al, 1998). The spatial pattern of the fibers demonstrated in this study also overlaps in part the pattern of elastin immunoreactivity in the limb bud (Hurle et al, 1994;Ros et al, 1995;Hurle and Colombatti, 1996), but appears to be more comparable to the pattern of emilin (Hurle and Colombatti, 1996), which is known to be localized in the elastin-microfibril interface (Bressan et al, 1993). On the basis of these and other findings in this study, we discuss the functional and developmental significance of a parallel spatial array of extracellular subectodermal microfibrils.…”
supporting
confidence: 61%
“…By combining immunolabeling of specific elastic components with the use of whole-mount specimens we were able to discern important features undetected in previous studies of the heart extracellular matrix. We found that the valvular leaflets contain all the elastic components described in studies of other typical elastic fetal or adult tissues (Sakai et al, 1986;Bressan et al, 1993) including elastin, fibrillin, emilin, and collagen type VI, a component not always associated with elastic matrices (Knight et al, 1984;Sakai et al, 1986). Each of these components exhibited a fibrillar pattern in the atrioventricular valve leaflets oriented in the direction of the blood flow.…”
Section: Third Periodmentioning
confidence: 73%
“…The most characteristic feature of this period is the formation of a prominent elastic layer in the wall of the outflow tract of the heart. This elastic matrix contains primarily elastin, and is associated with fibrillin and emilin as observed in several fetal and adult elastic matrices (Sakai et al, 1986;Bressan et al, 1993), but appears to lack collagen type VI. The presence of elastin in the heart at these stages has been previously reported by Rosenquist et a1 (1988).…”
Section: Second Periodmentioning
confidence: 85%
See 1 more Smart Citation
“…As the name suggests, EMILIN-1 is found in elastin-rich tissues and is localized to the interface between amorphous elastin and microfibrils. Anti-EMILIN-1 antibodies promote the formation of elastin aggregates rather than fibers in SMC cultures (Bressan et al, 1993). EMILIN-1 binds elastin in solid-phase binding assays and both elastin and fibulin-5 in immunoprecipitation assays (Zanetti et al, 2004).…”
Section: Elastin Microfibril Interface Located Protein (Emilin)-1mentioning
confidence: 99%